Valour for Money? Contested Commodification in the Market for Security. (27th February 2018) - Loader, Ian; White, Adam
Abstract: Scholars of security governance generally assume that the labour of private security officers can straightforwardly be transformed into discrete commodities. We argue, by contrast, that it is extremely difficult to commodify the labour of private security officers because their duties frequently require them to confront and work through both economic responsibilities (what does my contract say?) and moral obligations (what does my conscience say?). We substantiate this argument by exploring how heroic acts performed by private security officers—such as preventing suicide attempts, intervening in violent assaults and orchestrating hazardous evacuations—are celebrated through industry awards ceremonies. In so doing, we not only contribute towards the conceptualization of security goods as contested commodities but also facilitate a reappraisal of the market for security.